2011
DOI: 10.1007/s10811-011-9656-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nutrient availability on understory algae during El Niño Southern Oscillation (ENSO) conditions in Central Pacific Baja California

Abstract: An experimental study of the effect of artificial nutrient supply on understory algae was made during 1997 El Niño Southern Oscillation (ENSO) at the Mexican Pacific coast of Baja California. Twelve quadrats of 1 m 2 were placed on the sea bed. Six quadrats were used as controls, and six were treatments with added artificial nutrients. Nutrients were supplied using polyvinyl chloride (PVC) pipes filled with slow-release inorganic fertilizer. The algae species composition and cover in each quadrat were estimate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 33 publications
1
8
0
1
Order By: Relevance
“…The relaxation of the spring to late summer upwelling regime along the Iberian Peninsula seems, therefore, to simultaneously affect both nutrient supply and ocean temperatures, with potential consequences for macroalgal eco‐physiology. For example, nutrients directly affect recruitment and survival of juvenile sporophytes of the ‘giant kelp’ Macrocystis pyrifera , particularly during El Niño events, characterized by warm and nutrient‐poor waters (Hernández‐Carmona, Riosmena‐Rodríguez, Serviere‐Zaragoza, & Ponce‐Díaz, ).…”
Section: Introductionmentioning
confidence: 99%
“…The relaxation of the spring to late summer upwelling regime along the Iberian Peninsula seems, therefore, to simultaneously affect both nutrient supply and ocean temperatures, with potential consequences for macroalgal eco‐physiology. For example, nutrients directly affect recruitment and survival of juvenile sporophytes of the ‘giant kelp’ Macrocystis pyrifera , particularly during El Niño events, characterized by warm and nutrient‐poor waters (Hernández‐Carmona, Riosmena‐Rodríguez, Serviere‐Zaragoza, & Ponce‐Díaz, ).…”
Section: Introductionmentioning
confidence: 99%
“…Hernández‐Carmona et al . (2011) found significant differences in coverage of P. torreyi sampled in the same region, in relation to temperature and nutrient changes associated with El Niño.…”
Section: Discussionmentioning
confidence: 93%
“…It has also been reported that eutrophication can result in increased abundance of ephemeral and filamentous algae (for example, Enteromorpha) (Worm et al 2002;Worm and Lotze 2006). Hernández-Carmona et al (2011) conducted an experiment on the effect of artificial nutrient supply on understory algae during the 1997 ENSO at the Mexican Pacific coast of Baja California and concluded that eight species of algae and one seagrass, among 26 species, had a positive response to the nutrients. Further study on the effect of nitrate supply on seaweed communities is needed to develop this essential means for kelp enhancement during the recent global warming situation.…”
Section: Discussionmentioning
confidence: 99%